A New Lichen-Forming Fungus, Aspicilia humida, from a Forested Wetland in South Korea, with a Taxonomic Key for Aspicilioid Species of Korea. Issue 1 (2nd January 2022) - Lee, Beeyoung Gun; Shin, Hyun Tak; Hur, Jae-Seoun
Abstract: Aspicilia humida Lee is described as a new lichen-forming fungus from a wetland forest, South Korea. The new species is distinguishable from Aspicilia aquatica (Fr.) Körb., the most similar species, by the absence of prothallus, black disk without green color in water, olive-brown epihymenium, shorter hymenium, hymenium I + yellowish blue-green, wider paraphysial tips without a vivid pigment, smaller asci, smaller ascospores, and the presence of stictic acid. Molecular analyses employing internal transcribed spacer (ITS) and mitochondrial small subunit (mtSSU) sequences strongly support A. humida as a distinct species in the A. cinerea group. A surrogate key is provided to assist in the identification of all 28 aspicilioid species of Korea.